RADIOTHERAPY MANAGEMENT IN CLINICAL SYNONASAL CANCER AT THE RADIOTHERAPY INSTALLATION OF ARIFIN ACHMAD HOSPITAL, RIAU PROVINCE - Afianti Nurfadilla; Neng Asih; Dilla Anggraini (LPPM Universitas Awal Bros, 2025)
Background: Sinonasal cancer is a malignancy that originates in the nasal cavity or paranasal sinuses. One treatment modality is external radiotherapy, which uses radiation to control or destroy cancer cells. Radiotherapy implementation requires several stages to ensure targeting accuracy and therapy safety. Objective: To determine the management of radiotherapy in patients with clinical sinonasal cancer in the Radiotherapy Installation of Arifin Achmad Regional Hospital, Riau Province. Methods: This study used a descriptive qualitative method with a case study approach. Data collection was conducted in June 2024 through observation, documentation studies, and interviews with medical physicists and radiotherapists. The study sample was one patient diagnosed with stage T4N0M0 sinonasal cancer. Results: Radiotherapy management included consultation with a radiation oncologist, simulation using a CT simulator, fabrication of fixation devices, determination of reference points, target contouring, dose planning using the Treatment Planning System (TPS), geometry verification, portals, and irradiation using a Linear Accelerator (LINAC). The patient received a total dose of 70 Gy, delivered in three phases: 27 × 2 Gy, 3 × 2 Gy, and 5 × 2 Gy, with two isocenters. Conclusion: Radiotherapy management for sinonasal cancer at Arifin Achmad Regional Hospital, Riau Province, was carried out in stages, starting with consultation, CT simulation, contouring, TPS planning, geometry verification, portal placement, and irradiation using the LINAC. Each stage was carried out to ensure the accuracy of radiation delivery to the target therapy.